If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + 3x = -25 Reorder the terms: 4(-1 + x) + 3x = -25 (-1 * 4 + x * 4) + 3x = -25 (-4 + 4x) + 3x = -25 Combine like terms: 4x + 3x = 7x -4 + 7x = -25 Solving -4 + 7x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 7x = -25 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = -25 + 4 7x = -25 + 4 Combine like terms: -25 + 4 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| (x+3)(x-6)-(x+2)(x-7)= | | 5x+5=3-(7x-7) | | 4(x+2)+2x=26 | | 6-4(4x-5)=14 | | -2(x+4)=-12 | | y+8x=102 | | 4(3x+2)=48 | | 6x+2=-6+4x+22 | | 5-7(4-7x)=0 | | 7-3(2x+9)=4 | | 4(6x-10)=80 | | 12=-t+4 | | 3(x+2)-2=16 | | -56/14 | | -5/4(12x-16)=-25 | | 5(3x-7)-2(x+3)-15x= | | 2(2x-x)=106 | | v=3.14(9)(100) | | f(-15)=3x-9 | | 5(x+2m+7)= | | f(-8)=3x-9 | | -5x+6x+10x-1x= | | f(9)=3x-9 | | X/7-6=30 | | y^2-2xy-3x=0 | | 3(2x)-12=0 | | 2x^2+6-71=0 | | f(12)=3x-9 | | 81-(a-3)= | | 2(2x-3)+1=-3x+7(x-2) | | 2x+6x=64 | | X(-4)=-20 |